A multi‐method evaluation of the implementation of a cancer teamwork assessment and feedback improvement programme (MDT‐FIT) across a large integrated cancer system. (21st January 2021) - Taylor, Cath; Harris, Jenny; Stenner, Karen; Sevdalis, Nick; Green, James SA
Abstract: Background: Globally, Multidisciplinary Teams (MDTs) are considered the gold standard for diagnosis and treatment of cancer and other conditions, but variability in performance has led to demand for improvement tools. MDT‐FIT (Multidisciplinary Team Feedback for Improving Teamwork) is an improvement programme developed iteratively with over 100 MDTs (≥1100 MDT‐members). Complex interventions are often adapted to context, but this is rarely evaluated. We conducted a prospective evaluation of the implementation of MDT‐FIT across an entire integrated care system (ICS). Methods: MDT‐FIT was implemented within all breast cancer MDTs across an ICS in England ( n  = 10 MDTs; 275 medical, nursing, and administrative members). ICS managers coordinated the implementation across the three stages of MDT‐FIT: set up; assessment (self‐report by team members plus independent observational assessment); team‐feedback and facilitated discussion to agree actions for improvement. Data were collected using process and systems logs, and interviews with a purposively selected range of participants. Analysis was theoretically grounded in evidence‐based frameworks for implementation strategies and outcomes. Results: All 10 MDTs participated in MDT‐FIT; 36 interviews were conducted. Data from systems and process logs covered a 9‐month period. Adaptations to MDT‐FIT by the ICS (e.g., coordination of team participation by ICS rather than individual hospitals; and reducing time protected for coordination) reduced Fidelity and Adoption of MDT‐FIT. However, the Acceptability, Appropriateness and Feasibility of MDT‐FIT remained high due to embedding implementation strategies in the development of MDT‐FIT (e.g., stakeholder engagement, interactive support). Conclusions: This is a unique and comprehensive evaluation of the multi‐site implementation of a complex team improvement programme. Findings support the imperative of considering implementation strategies when designing such programmes to minimize potentially negative impacts of adaptations in "real world" settings. Abstract : This paper describes the prospective evaluation of the real world implementation of a cancer team improvement programme (MDT‐FIT) across an entire integrated care system, to inform the adaptation vs. fidelity debate in complex interventions. Although adaptations to the programme by the ICS reduced fidelity and adoption of MDT‐FIT, acceptability, appropriateness and feasibility were high due to embedding of implementation strategies (such as stakeholder engagement) in the development of the programme, and reinforce the imperative of such strategies in the design of complex programmes.